ANALISIS KEPUTUSAN INVESTASI WARUNG INTERNET ATAU NETWORKING GAME CENTER DENGAN DECISION TREE ANALYSIS - Herlambang, Tony
Abstract : Nowadays the rapid development of internet function in the modern world and internet connection technology generate the need of internet services. In fact the increasing of living costs makes a new business opportunities such as cyber cafes. These can fulfil the need of internet services with relatively cheaper cost and faster intemet access than if we access it from home with dial up connection. An additional cost is needs for telephone bill. Another development from entertainment section is networking game, even though on locally networking or using internet on networking game. This kind of business is usually called networking game center or just game center. Technically, two kinds of these business have similarity in the need of investment, but cyber cafe needs an additional investment such as internet connection devices and connection fees. The main idea of these studies is to analyze investment decision between cyber cafe investment or networking game center investment and to decide how much the investor should invest theirs money. Basically investments are divided into 2 category. There are big investment (30 pc) and small investment (15 pc). These studies use decision tree analysis method for solving the investment problem. From Decision Tree Analysis, we can know the expected value of NPV (Net Present Value) from each alternative decisions. So that the best alternative decision which have the biggest expected value of NPV by comparing each alternative decisions in decision tree roll back process. Then the next step is the sensitivity analysis to explore the effects/influences of future possible changes from what is assumed before to the picked decision. The result of this analysis shows that big investment on networking game center will be the best option. These result was restricted by constraint, decision tree diagram model, and some assumptions that analyst declared.